Pesantren Community Paradigm Towards The Practice of Religious Moderation in West Sumatra - Zainal, Zainal; Mohamed Sidik, Mohd Suhadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The Government's efforts to find a formula for religious coolness have found momentum with the popular idea of Religious Moderation. This term is the main mission of Islam in realizing people who live in peace and provide benefits to others. This study aims to reveal the paradigm of the pesantren community towards the practice of Religious Moderation in West Sumatra. Community acceptance of the Religious Moderation discourse is due to several approaches that are easy to understand and prioritize aspects of local wisdom. The method used in this research is qualitative with a descriptive analysis approach to describe and explain the acceptance of pesantren communities in West Sumatra towards the practice of Religious Moderation. The results of this study can be concluded that in terms of values, the application of Religious Moderation has long been applied by exploring lessons sourced from the book of turast. While at the practice stage it still requires intense strengthening and education to the community in order to understand the benefits of applying this concept. The Moderate perspective has a positive impact when brought to a wider area, especially inter-religious relations. The contribution of this research can be used as a basis for policy makers (stakeholders) in formulating strategic plans in the field of community religion. Upaya Pemerintah dalam menemukan formula kesejukan beragama telah menemukan momentumnya dengan gagasan populer yaitu Moderasi Beragama. Term ini merupakan misi utama Islam dalam mewujudkan umat yang hidup damai dan memberikan manfaat kepada orang lain. Penelitian ini bertujuan untuk mengungkap paradigma komunitas pesantren terhadap praktek Moderasi Beragama di Sumatera Barat. Penerimaan masyarakat terhadap wacana Moderasi Beragama disebabkan oleh beberapa pendekatan yang dilakukan mudah dipahami dan mengutamakan aspek kearifan lokal. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan deskriptif analisis untuk menggambarkan dan menjelaskan penerimaan komunitas pesantren di Sumatera Barat terhadap praktek Moderasi Beragama. Hasil penelitian ini dapat disimpulkan bahwa secara nilai-nilai, penerapan Moderasi Beragama telah lama diterapkan dengan menggali pelajaran yang bersumber dari kitab turast. Sedangkan pada tahapan praktek masih memerlukan penguatan dan edukasi yang intens kepada masyarakat agar memahami manfaat dari penerapan konsep ini. Cara pandang Moderat berdampak positif ketika dibawa ke area yang lebih luas terutama hubungan antar umat beragama. Kontribusi dari penelitian ini dapat dijadikan sebagai dasar pengambil kebijakan (stakeholders) dalam merumuskan rencana strategis dalam bidang keagamaan masyarakat.